Obsessive compulsive symptom dimensions and neuroticism: An examination of shared genetic and environmental risk. Issue 8 (17th September 2014) - Bergin, Jocilyn; Verhulst, Brad; Aggen, Steven H.; Neale, Michael C.; Kendler, Kenneth S.; Bienvenu, Oscar J.; Hettema, John M.
<x xml:space="preserve">Abstract</x> Individuals with obsessive compulsive disorder can display diverse and heterogeneous patterns of symptoms. Little is known about the relationship between obsessive‐compulsive symptom (OCS) dimensions and normal personality traits, particularly those that increase risk for other internalizing disorders. In this study of 1, 382 individuals from female–female twin pairs, we examined the relationship between self‐report OCS dimensions derived from the Padua Inventory and Eysenck's personality traits neuroticism and extraversion. We conducted factor analysis to determine their phenotypic structure followed by twin analyses to determine their genetic and environmental sources of covariation. A three‐factor solution, with dimensions corresponding to checking, aggressive obsessions, and contamination, was the best fit for the Padua OCS items. These dimensions were significantly and somewhat variably associated with neuroticism but negligibly associated with extraversion. The genetic correlations between neuroticism and these three OCS dimensions were moderate to high (0.66 with checking, 0.89 with aggressive obsessions, and 0.40 with contamination). However, the estimated genetic correlation between neuroticism and a unified latent OCS construct was smaller (0.32). Overall this study suggests that genetic, and to a smaller extent environmental, factors underlying neuroticism may act differentially as risk factors for OCS dimensions. © 2014 Wiley Periodicals, Inc.